Gingival Melanin Depigmentation by 808 nm Diode Laser: Report of a Case - Jade Chagra; Adel Bouguezzi; Sameh Sioud; Hajer Hentati; Jamil Selmi (Case Reports in Dentistry)
Gingival hyperpigmentation frequently poses an aesthetic problem, especially in patients with gingival smile. This paper presents the use of a 808 nm pulsed diode laser for gingival depigmentation in a 22-year-old male patient, with a frequency of 20,000 Hz, a peak power of 5 W, and a pulse width of 26 microseconds, using a 400 nm flexible optic fiber. The hyperpigmented gingival tissue was removed without bleeding or postoperative pain. Three weeks later, the gum resumed its normal, firm, and pink appearance. No significant recurrence was noted after a follow-up of 4 months. However, perfect control of this device is necessary to avoid certain consequences such as bone exposure or gingival fenestrations.